(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2017)
The history of the socialist political movement in Malaya has always been identified as having similarities with the history of the communist political ideology. This misconception has influenced the general understanding of the socialist movement struggles and developments in Malaya, especially those related to the radical movements and the Malay political developments in Malaya. Hence, this article focuses on the development of the socialist political ideology as an influence of the Indonesian Socialist Marxism which became a basis for the socialist ideology development by the left-wing Malay radical nationalist movements in their class political survival from 1925 to 1948. Through the history of Reconstructionist and the hermeneutic interpretation approach, the analysis and discussion is developed based on the primary sources such as the British documents as well as the secondary sources to support the arguments. It is found that the socialist ideological influences developed in two forms, i.e. Socialist Marxism and Reformist Marxism through PKMM, API, AWAS, PETA and BATAS. In its Malayan context, this ideology developed as a result of the framework established by Alimin and Tan Malaka world view who formed a radical ideology among the Malay political actors which is different from the Reformist Marxism. This article highlights a different angle based on the interpretation of the primary sources itself and the modern political approach in describing the historical developments of the socialist ideology in Malaya. Sejarah gerakan politik aliran sosialis di Tanah Melayu sering digambarkan mempunyai persamaan dengan fahaman politik komunis. Kemelut pandangan ini secara tidak langsung memberi kesan terhadap kefahaman perkembangan dan perjuangan politik aliran sosialis di Tanah Melayu, terutama yang mengaitkan gerakan radikal nasionalisme dengan pembangunan politik Melayu di Tanah Melayu. Sehubungan itu, makalah ini menumpukan kepada perkembangan ideologi politik aliran sosialis melalui pengaruh Sosialis Marxisme dari Indonesia yang menjadi asas perkembangan aliran sosialis dalam kalangan gerakan aliran kiri nasionalis radikal Melayu dalam meneruskan keberlangsungan politik kelas sepanjang tahun 1925 sehingga tahun 1948. Dengan menggunakan pendekatan Reconstructionist sejarah dan interpretasi hermeunitik, analisis perbincangan dikembangkan berdasarkan penggunaan sumber primer sebagai asas hujah, terutama dokumen British, di samping sumber-sumber sekunder yang lain. Dapatan kajian mendapati pengaruh aliran sosialis berkembang dalam dua bentuk aliran, iaitu Sosialis Marxisme dan Reformis Marxisme melalui PKMM, API, AWAS, PETA dan BATAS. Dalam konteks Tanah Melayu, perkembangan aliran ini secara dasarnya dikerangkakan oleh sudut pandang Alimin dan Tan Malaka yang membentuk fahaman radikal dalam kalangan aktor-aktor politik Melayu dan membezakannya antara komunis Sosialis Marxisme dengan Reformis Marxisme. Makalah ini menterjemahkan satu sisi yang berbeza berdasarkan tafsiran sumber utama itu sendiri dan pendekatan politik moden dalam menjelaskan perkembangan aliran sosialis di Tanah Melayu.